DRAMATIZATION STRATEGY AND JUNIOR HIGH SCHOOL STUDENTS’ READING MOTIVATION - Vismaia Sabariah Damaianti (Universitas Negeri Makassar, 2021)
This study is motivated by many expert opinions which state that the students' reading motivation in Indonesia still needs to be increased. The researcher tries to answer the problem by trying out a Dramatization Strategy in reading learning with the aim of increasing reading motivation. This strategy is carried out by developing students' cognitive and metacognitive abilities. The experimental method with a factorial design is chosen to determine the effectiveness of the Dramatization Strategy, either for readers with high- or low-level reading comprehension. The data sources of this study are 101 students of Madrasah Tsanawiyah in Bandung Regency and Bandung City. The results of the study show that the Dramatization Strategy is effective in increasing reading motivation, especially for improving reading skills and for social interaction. The implication of the study is the need for the application of the dramatization strategy by adjusting the teachers’ insights and abilities in identifying students' reading motivation.